INTEGRATION OF COMPUTER TECHNOLOGY INTO THE ADVANCED MASTERY OF THE DISCIPLINE "DESCRIPTIVE GEOMETRY AND ENGINEERING GRAPHICS" BY UNIVERSITY STUDENTS - AFTANAZIV, IVAN; KOMAROV, SERHII; STROHAN, ORYSIA; SVIDRAK, INHA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
This paper presents an analytical study on the effectiveness of integrating computer technology into the educational process during the instruction of graphic disciplines for full-time university students. The experimental sociological research was conducted based on the outcomes of mastering the discipline descriptive geometry and engineering graphics by students enrolled in the 237 "transport technologies" specialty at the institute of mechanical engineering and transport, lviv polytechnic national university, during the spring semester of the 2024–2025 academic year. According to the curriculum of the corresponding educational and professional program, the discipline is allocated 5 ects credits, amounting to a total workload of 150 hours, of which 60 hours are designated for in-class instruction, with the remaining time allocated for students’ independent study. To incorporate sociological variables into the analysis, the students’ academic performance outcomes were disaggregated by gender and by the mode of completing examination tasks — with either full or partial use of computer technology. The results of the study reveal that the application of computer technology in the learning process significantly enhances students’ academic achievements and contributes to a deeper comprehension of the course content. Of particular note are the performance indicators of the cohort that employed computer technology to the fullest extent (100%) in completing examination assignments. Their academic quality indicators exceeded those of their peers by 20–25%, underscoring the pedagogical efficacy of integrating computational tools into the study of descriptive geometry and engineering graphics.